Kemampuan Pemecahan Masalah Matematis Peserta Didik yang Memiliki Habits of Mind:Thinking Interdependently (HTI) ditinjau dari Kemampuan Matematika Sedang dan Rendah - Aura Alivana, Rizky Putri; Masriyah, Masriyah (MATHEdunesa, 2025)
This research aims to determine the mathematical problem solving skills of students who have same percentage of HTI score but have different mathematical skills namely medium and low mathematical skills. The method used is descriptive qualitative with output descriptions of the mathematical problem solving skills possessed by the two research subjects. The data obtained came from HTI questionnaire, mathematical skills tests, mathematical problem solving skills test, and interviews conducted with selected subjects. The results showed that subject with medium mathematical skills could understand the problem well, could plan appropriate strategies, but made mistakes in implementing the strategy and carrying out re-examination. Meanwhile, subject with low mathematical skills can understand the problem well, cannot plan and implement a strategy appropriate to the problem, but can re-examine the steps taken. Thus, the problem solving abilities of student with moderate HTI and mathematical skills is better than students with low mathematical skills even though they have the same percentage of HTI scores.